Self-efficacy and digital anxiety and their influence on virtual educational performance - Iraola Arroyo, Juan Alonso (2023)
Digital self-efficacy is the degree of confidence to efficiently use technological tools. This type of self-efficacy reduces digital anxiety and increases students' performance in virtual environments. This justifies the objective of the present research, which is to analyze the levels of self-efficacy and digital anxiety, as well as their influence on virtual educational performance in students of a private university in Lima, Peru. Using a non-probabilistic convenience sampling procedure, 116 students participated, 105 females (90.5%) and 11 males (9.5%) between 17 and 50 years of age (MeanAge = 26.78, SD = 7.02). The results showed that students perceived to agree in having optimal levels of digital self-efficacy and efficient virtual educational performance. However, they indicated neither agreement nor disagreement in feeling digitally anxious. In addition, it was observed that digital self-efficacy is related to virtual educational performance; and digital anxiety was higher in the older study cycles. The results dispute the concept of "digital native" because age was not related to high levels of self-efficacy, digital performance, or low levels of digital anxiety.